A study of the effect of PEG-1000 phase change materials coating on selected fabric properties. (30th September 2022) - Niles, Nilhan; Vijayarajah, Vithursha
Phase change materials (PCM) are materials that are used as latent heat storage media due to their ability to undergo change from one phase to another. The use of PCM to enhance the temperature self-regulating feature of textiles has become prevalent in recent times. A PCM is incorporated into the textile substrate using various means, one of which is coating. However, the process of coating the textile substrate with the PCM material, as well as the effect of the material itself, may result in the reduction of certain key properties of the textile material. The aim of this study is to examine the effect of a Sodium Alginate microencapsulated PEG-1000 coating (applied by the pad-dry-cure method) on selected properties of a 100% polyester single jersey knitted fabric, namely bursting strength, thickness, drape coefficient, air permeability, moisture regain and fabric weight. The material and coating were selected on the basis of availability, use and cost. The study showed that the coating provided small increases in the bursting strength, weight, moisture regain and thickness, and a substantial increase in the drape coefficient of the fabric. The air permeability could not be properly assessed due to an instrument error. As such the coating could be presumed to have caused a slight impairment to the overall comfort of the fabric.